2017
DOI: 10.1007/s10265-017-0926-4
|View full text |Cite
|
Sign up to set email alerts
|

A root penetration model of Arabidopsis thaliana in phytagel medium with different strength

Abstract: Phytagel media were evaluated as systems to mechanically impede roots of A. thaliana. Studying mechanical properties of Phytagel and exploring the root response to mechanical stimulation can facilitate plant culture and plant development. Breaking strengths of 0.5-2.0% phytagel media were tested by uniaxial compression test. Different phytagel concentrations were set to alter the strength of layers in growth medium. Negative correlations were observed between root length, straightness and medium strength. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…Root bending has also been observed in roots grown in a medium consisting of a soft upper layer and a hard lower layer. The root exhibits a bending response at the lower, harder layer (Yamamoto et al, 2008;Yan et al, 2017Yan et al, , 2018. It has been suggested that a zone of 'mechanical weakness' is required for the bending process and that this is localised between the growing and mature zones of the root (Bizet et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Root bending has also been observed in roots grown in a medium consisting of a soft upper layer and a hard lower layer. The root exhibits a bending response at the lower, harder layer (Yamamoto et al, 2008;Yan et al, 2017Yan et al, , 2018. It has been suggested that a zone of 'mechanical weakness' is required for the bending process and that this is localised between the growing and mature zones of the root (Bizet et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Different from typical solid agar-based media, highly thermostable Phytagel, which can remain solid for 1 h at 120°C, was used for screening in directed evolution. To the best of our knowledge, Phytagel was normally used for the cultivation and isolation of hyperthermophilic bacteria (43) or plant tissue (44). Herein, we adopted it for the application of Phytagel-based plates as a thermotolerant gelling agent to replace the use of agar plates at enzyme engineering for enhanced thermostability by directed evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Agar-based phenotyping does have some drawbacks. Agar must be prepared to a resistance similar to that of soil so that roots can penetrate and adequate structural support is provided for the plant [84]. Agar, while a solid, does not have pore space like soil, which may influence root growth.…”
Section: Lab and Greenhouse-based Phenotyping For Root System Architementioning
confidence: 99%
“…Agar, while a solid, does not have pore space like soil, which may influence root growth. Seeds inserted fully into agar can become sealed and lack enough gas exchange to promote germination [84]. Varying methods of planting have been utilized for gel-based systems to combat these problems.…”
Section: Lab and Greenhouse-based Phenotyping For Root System Architementioning
confidence: 99%